Orofacial Pain during Mastication in People with Dementia: Reliability Testing of the Orofacial Pain Scale for Non-Verbal Individuals - Lobbezoo, Frank; Scherder, Erik J. A.; Pieper, Marjoleine J. C.; van der Steen, Jenny T.; Delwel, Suzanne; Visscher, Corine; de Vries, Merlijn W.; Achterberg, Wilco P. (Behavioural neurology, 2016)
Objectives. The aim of this study was to establish the reliability of the “chewing” subscale of the OPS-NVI, a novel tool designed to estimate presence and severity of orofacial pain in nonverbal patients. Methods. The OPS-NVI consists of 16 items for observed behavior, classified into four categories and a subjective estimate of pain. Two observers used the OPS-NVI for 237 video clips of people with dementia in Dutch nursing homes during their meal to observe their behavior and to estimate the intensity of orofacial pain. Six weeks later, the same observers rated the video clips a second time. Results. Bottom and ceiling effects for some items were found. This resulted in exclusion of these items from the statistical analyses. The categories which included the remaining items (n=6) showed reliability varying between fair-to-good and excellent (interobserver reliability, ICC: 0.40–0.47; intraobserver reliability, ICC: 0.40–0.92). Conclusions. The “chewing” subscale of the OPS-NVI showed a fair-to-good to excellent interobserver and intraobserver reliability in this dementia population. This study contributes to the validation process of the OPS-NVI as a whole and stresses the need for further assessment of the reliability of the OPS-NVI with subjects that might already show signs of orofacial pain.